2016
DOI: 10.1002/ca.22718
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the long head of biceps femoris: An ultrasound study

Abstract: Hamstring strains, particularly involving the long head of biceps femoris (BFlh) at the proximal musculotendinous junction (MTJ), are commonly experienced by athletes. With the use of diagnostic ultrasound increasing, an in‐depth knowledge of normal ultrasonographic anatomy is fundamental to better understanding hamstring strain. The aim of this study was to describe the architecture of BFlh, using ultrasonography, in young men and cadaver specimens. BFlh morphology was examined in 19 healthy male participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 54 publications
5
31
0
Order By: Relevance
“…Such values are in accordance with previous studies using US on other muscles, suggesting that errors from measurements do not depend on the muscles studied as much as other factors (eg, rater assessment procedures). Fascicle length, fascicle angle, and muscle thickness measurement reliability rates were similar to those reported previously . In this study, values of 9.6 ± 18.0 cm, 12.4 ° ± 2.8 °, and 2.0 ± 0.4 cm were obtained in the full‐image width for the fascicle length, fascicle angle, and muscle thickness, respectively, whereas in previous studies, values of 5.9 ± 0.3 to 8.8 ± 1.8 cm, 14.9 ° ± 3.3 ° to 23.9 ± 3.8 °, and 1.3 ± 0.2 to 2.7 ± 0.3 cm were reported.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Such values are in accordance with previous studies using US on other muscles, suggesting that errors from measurements do not depend on the muscles studied as much as other factors (eg, rater assessment procedures). Fascicle length, fascicle angle, and muscle thickness measurement reliability rates were similar to those reported previously . In this study, values of 9.6 ± 18.0 cm, 12.4 ° ± 2.8 °, and 2.0 ± 0.4 cm were obtained in the full‐image width for the fascicle length, fascicle angle, and muscle thickness, respectively, whereas in previous studies, values of 5.9 ± 0.3 to 8.8 ± 1.8 cm, 14.9 ° ± 3.3 ° to 23.9 ± 3.8 °, and 1.3 ± 0.2 to 2.7 ± 0.3 cm were reported.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, a detailed report of a reliability of assessment of the biceps femoris muscle architecture has not been presented previously . Chleboun et al reported high inter‐rater reliability (ICC = 0.87), whereas Kellis et al compared and characterized cadaveric versus US measurements to provide method validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These US measures display superior clinical utility, considering the change values in FL detailed above, compared to the 3.5 cm established by the current methods. As US measures of BFlh architecture have also compared favorably with direct cadaveric measurement, US measures of BFlh architecture continue to have superior evidence of robustness compared to the current DTI measures. Furthermore, poor agreement between DTI measures and US measures of FL can be observed in Table and Figure .…”
Section: Discussionmentioning
confidence: 99%